Growth Following Investment and Consumption-Driven Current Account Crises - Klemm, Alexander (IMF Working Papers; Working Paper, 2013)
Current account deficits imply increasing liabilities to the rest of the world. External sustainability then depends on whether these can be met in the future without defaulting, id est, normally through trade account surpluses. To run such surpluses without a fall in consumption, capital inflows should be used to increase future output. This paper tentatively finds that current account deficits reversals that follow investment booms are marked by better growth performance than those following consumption booms. It also shows that many recent large current account deficits have been predominantly the result of consumption or non-productive investment booms.